Uporaba kisikove sonde pri kontroli in vodenju procesa izdelave jekla - Koroušić, Blaženko (Kovine zlitine tehnologije, 1998)
Steelwork JEKLO-ŠTORE and METAL-RAVNE started using expendable probes for the determination of the active oxygen content in early 1980. Since January 1997, the shops have been determing and controlling the oxygen content of the bath at turndown at almost every heat. The oxygen content is used to determine the carbon level before LF - practice or for optimal determination the deoxidationand alloy addition schedules for most steel grades. Through the use of oxygen probes, tighter carbon and oxygen control in electric-arc furnace (EAF) can be made but also quality and yield have been improved.
Keywords: jeklo; kisik; merjenje; talina